Lignocellulosic biomass-derived, graphene sheet-like porous activated carbon for electrochemical supercapacitor and catechin sensing. Issue 72 (25th September 2017) - Veeramani, Vediyappan; Sivakumar, Mani; Chen, Shen-Ming; Madhu, Rajesh; Alamri, Hatem R.; Alothman, Zeid A.; Hossain, Md. Shahriar A.; Chen, Ching-Kuo; Yamauchi, Yusuke; Miyamoto, Nobuyoshi; Wu, Kevin C.-W.
Abstract : We synthesize graphene sheet-like porous activated carbon (GPAC) with a high specific surface area by using Bougainvillea spectabilis as a precursor with the assistance of a facile and reliable chemical activation method. Abstract : We synthesize graphene sheet-like porous activated carbon (GPAC) with a high specific surface area by using Bougainvillea spectabilis as a precursor with the assistance of a facile and reliable chemical activation method. The as-synthesized GPAC materials were characterized with a variety of physico-chemical and analytical techniques to investigate their structural and porous properties. In addition, we apply the synthesized GPAC as an electrode material for supercapacitor and catechin sensing, and corresponding electrochemical studies were carried out using cyclic voltammetry, galvanostatic charge–discharge and differential pulse voltammetry. For supercapacitor application, the GPAC exhibits a specific capacitance of 233 F g −1 (at a current density of 1.6 A g −1 ) and an energy density of 7.2 W h kg −1 (for a symmetric cell). For the sensing application, the GPAC exhibits sensitive detection of catechin (CA). We achieved good sensitivity, an extensive linear range, and a low limit of detection for the CA sensor, with values of 7.2 μA μM −1 cm −2, 4–368 μM, and 0.67 μM, respectively. We further test the GPAC sensor in green tea leaves for real time CA detection. This work demonstrates the successful conversion of waste biomass to useful electrochemical devices.